Development of a Web-Based CBT Worksheet for Routine Motorcycle Maintenance - Naufal; Arwizet K; Wawan Purwanto; Ika Parma Dewi; Abdul Habib Arrasyidi Desky (Jurnal Penelitian Pendidikan IPA, 2026)
This study aimed to develop a web-based electronic jobsheet system for the periodic motorcycle service subject at SMK Negeri 4 Palembang using the ADDIE model. The development was motivated by the continued use of paper-based practical assessment, which limits documentation and digital integration in vocational learning. The system integrates learning materials, digital jobsheets, procedural checklists, evidence uploads, and assessment features within a platform. The study employed the ADDIE stages of Analysis, Design, Development, Implementation, and Evaluation. Effectiveness testing was conducted during the implementation phase involving 66 Grade XI Motorcycle Engineering students, consisting of 32 students in the experimental class and 34 students in the control class. Data were collected through validation sheets, practicality questionnaires, and pre-test/post-test instruments. The developed system achieved an average validity score of 94.44% and a practicality score of 84.21%, categorized as Very Valid and Very Practical. Learning outcomes in the experimental class improved based on the Paired Sample t-test, with mean scores increasing from 80.28 to 90.16. The N-Gain score was 0.42, categorized as moderate, and slightly higher than the control class score of 0.39. Practical performance was higher, with mean scores of 89.23 and 78.41 respectively. These findings indicate that the developed system is effective.